Development of a Novel Cytochrome b Real-Time PCR Assay for Identification of Plasmodium malariae - Thi Thu Hang, Dinh; Thi Nga, Vu; Van Tong, Hoang; Xuan Su, Hoang; Quoc Tuan, Le; Van Chuyen, Nguyen; Thi Minh Trinh, Nguyen; Anh Son, Ho (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 3, 2020)
This article aims to establish a novel cytochrome b real-time PCR assay using Taqman probe for identification of P. malariae and its discrimination from other Plasmodium human infecting species. The optimization of real-time PCR assay with 1X QuantiTect Probe PCR Master Mix, primers and probe used at concentrations of 0.4 μM and 0.1 μM, respectively; and 2.5 mM MgCl 2 , 5 μl DNA template and deionized H 2 O of 20 μl, was performed using a real-time PCR instrument. The developed real-time PCR assay was evaluated for the limit of detection, stability on standard panels (10 9 -10 0 copies/ µl), as well as the sensitivity, specificity on control groups. The probit analysis demonstrates that the 95% detection limit was <0.5 parasite/μl, both the sensitivity and specificity of the assay were 100% when evaluated on the control groups.  Additionally, the assay initially evaluated on 41 clinical samples including 21 malaria samples and 20 samples of volunteer blood donors, identified 1 positive sample with P. malariae from the disease group, which shows a concordant result with nested PCR. This novel Cyt b real-time PCR assay for identifying P. malariae may also facilitate earlier discrimination of P. malariae from other Plasmodium parasites with high sensitivity. Keywords Cytochrome b, malaria parasite, plasmodium malariae, mitochondria, real-time PCR. References [1] B. Singh, C. Daneshvar, Human infections and detection of Plasmodium knowlesi, Clinical microbiology reviews 26(2) (2013) 165-84. https://doi.org/10.1128/cmr.00079-12. [2] World Health Organization, Regional and global trends in burden of malaria cases and deaths, World malaria report 2019, Geneva, pp. 4-12. [3] World Health Organization, Progress towards elimination during the RBM decade 2000-2010, Eliminating malaria: learning from the past, looking ahead, Geneva (2011), pp. 39-70. [4] J.M. Vinetz, J. Li, T.F. McCutchan, et al., Plasmodium malariae infection in an asymptomatic 74-year-old Greek woman with splenomegaly, N Engl J Med 338(6) (1998) 367-71. https://doi.org/10.1056/NEJM199802053380605. [5] E. Lo, K. Nguyen, J. Nguyen, et al., Plasmodium malariae Prevalence and csp Gene Diversity, Kenya, 2014 and 2015, Emerg Infect Dis 23(4) (2017) 601-610. https://doi.org/10.3201/eid2304.161245. [6] W.E. Collins, G.M. Jeffery, Plasmodium malariae: parasite and disease, Clinical microbiology reviews 20(4) (2007) 579-92. https://doi.org/10.1128/CMR.00027-07. [7] M. Adams, S.N. Joshi, G. Mbambo, et al., An ultrasensitive reverse transcription polymerase chain reaction assay to detect asymptomatic low-density Plasmodium falciparum and Plasmodium vivax infections in small volume blood samples, Malar J 14 (2015) 520. https://doi.org/10.1186/s12936-015-1038-z. [8] W. Xu, U. Morris, B. Aydin-Schmidt, et al., SYBR Green real-time PCR-RFLP assay targeting the plasmodium cytochrome B gene-a highly sensitive molecular tool for malaria parasite detection and species determination, PloS one 10(3) (2015) e0120210. https://doi.org/10.1371/journal.pone.0120210. [9] E.M. Burd, Validation of laboratory-developed molecular assays for infectious diseases, Clinical microbiology reviews 23(3) (2010) 550-76. https://doi.org/10.1128/CMR.00074-09. [10] G. Snounou, S. Viriyakosol, X.P. Zhu, et al., High sensitivity of detection of human malaria parasites by the use of nested polymerase chain reaction, Molecular and biochemical parasitology 61(2) (1993) 315-20. https://doi.org/10.1016/0166-6851(93)90077-b. [11] C.G. Haanshuus, K. Morch, B. Blomberg, et al., Assessment of malaria real-time PCR methods and application with focus on low-level parasitaemia, PloS one 14(7) (2019) e0218982. https://doi.org/10.1371/journal.pone.0218982. [12] F. Perandin, N. Manca, A. Calderaro, et al., Development of a real-time PCR assay for detection of Plasmodium falciparum, Plasmodium vivax, and Plasmodium ovale for routine clinical diagnosis, Journal of clinical microbiology 42(3) (2004) 1214-9. https://doi.org/10.1128/jcm.42.3.1214-1219.2004. [13] C.E. Oriero, J.P. van Geertruyden, J. Jacobs, et al., Validation of an apicoplast genome target for the detection of Plasmodium species using polymerase chain reaction and loop mediated isothermal amplification, Clinical microbiology and infection : the official publication of the European Society of Clinical Microbiology and Infectious Diseases 21(7) (2015) 686 e1-7. https://doi.org/10.1016/j.cmi.2015.02.025. [14] D.F. Echeverry, N.A. Deason, J. Davidson, et al., Human malaria diagnosis using a single-step direct-PCR based on the Plasmodium cytochrome oxidase III gene, Malaria journal 15 (2016) 128. https://doi.org/10.1186/s12936-016-1185-x. [15] P. Li, Z. Zhao, H. Xing, et al., Plasmodium malariae and Plasmodium ovale infections in the China-Myanmar border area, Malaria journal 15(1) (2016) 557. https://doi.org/10.1186/s12936-016-1605-y. [16] E.T.J. Chong, J.W.F. Neoh, T.Y. Lau, et al., Genetic and haplotype analyses targeting cytochrome b gene of Plasmodium knowlesi isolates of Malaysian Borneo and Peninsular Malaysia, Acta tropica 181 (2018) 35-39. https://doi.org/10.1016/j.actatropica.2018.01.018. [17] C. Farrugia, O. Cabaret, F. Botterel, et al., Cytochrome b gene quantitative PCR for diagnosing Plasmodium falciparum infection in travelers, Journal of clinical microbiology 49(6) (2011) 2191-5. https://doi.org/10.1128/JCM.02156-10. [18] C. Wongsrichanalai, M.J. Barcus, S. Muth, et al., A review of malaria diagnostic tools: microscopy and rapid diagnostic test (RDT), The American journal of tropical medicine and hygiene 77(6 Suppl) (2007) 119-27. [19] H.V. Nguyen, P.V.D. Eede, C. van Overmeir, et al., Marked age-dependent prevalence of symptomatic and patent infections and complexity of distribution of human Plasmodium species in central Vietnam, The American journal of tropical medicine and hygiene 87(6) (2012) 989-995. https://doi.org/10.4269/ajtmh.2012.12-0047.